2000
DOI: 10.1038/35017500
|View full text |Cite
|
Sign up to set email alerts
|

Inspiration for optimization from social insect behaviour

Abstract: Research in social insect behaviour has provided computer scientists with powerful methods for designing distributed control and optimization algorithms. These techniques are being applied successfully to a variety of scientific and engineering problems. In addition to achieving good performance on a wide spectrum of 'static' problems, such techniques tend to exhibit a high degree of flexibility and robustness in a dynamic environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
364
0
16

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 800 publications
(382 citation statements)
references
References 25 publications
2
364
0
16
Order By: Relevance
“…However, the MCSDS algorithm (as deployed by Aunt Hillary) is unable to reliably play this way; to do so would require the anticipation of potential next moves from the opponent (see figure 3). To improve the tactical play, a metapopulation [23] of ants is deployed to enable a Monte-Carlo informed SDS to tactically explore the game tree 6 : Stochastic Diffusion Search applied to Trees (SDST).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the MCSDS algorithm (as deployed by Aunt Hillary) is unable to reliably play this way; to do so would require the anticipation of potential next moves from the opponent (see figure 3). To improve the tactical play, a metapopulation [23] of ants is deployed to enable a Monte-Carlo informed SDS to tactically explore the game tree 6 : Stochastic Diffusion Search applied to Trees (SDST).…”
Section: Discussionmentioning
confidence: 99%
“…In the study of interaction in social insects, two key elements are the individuals and the environment, which results in two modes of interaction: the first defines the way in which individuals interact with each other and the second defines the interaction of individuals with the environment [6]. Interaction between individual agents is typically carried out via agent recruitment processes and it has been demonstrated that various recruitment strategies are deployed by ants [19] and honey bees [15,32].…”
Section: Swarm Intelligencementioning
confidence: 99%
See 1 more Smart Citation
“…However, there are many other methods that have already been, or could be, applied to such problems: examples include antbased computation [73,74], evolutionary Kohonen networks [27*], fuzzy clustering [23], support vector machines [75] and Bayesian learning [66]. We believe that methods such as these will prove invaluable in the analysis of the huge volumes of data that characterise modern pharmaceutical research, particularly when used in combination [76**.77**].…”
Section: Discussionmentioning
confidence: 99%
“…The quantity of pheromone deposited, which may depend on the quantity and quality of the food, will guide other ants to the food source. Thus a shorter path tends to have a higher pheromone density, making it more likely to be chosen by other ants (Bonabeau et al 2000). This shortest path represents the global optimal solution and all the possible paths represent the feasible region of the problem.…”
Section: Using Aco To Solve Groundwater Management Modelmentioning
confidence: 99%